Frugal populists: fiscal management under populist rule in Europe and the OECD - Stankov, Petar (Frontiers in Political Science, 2025)
Populists weaponize economic hardships and identity conflicts for political gain. This strategy has propelled many of them to the political mainstream across Europe, the Americas, and elsewhere. However, does their toxic rhetoric necessarily map into poor management of government finances? This paper investigates one aspect of their governance—its correlation with government debt spanning the period between 1950 and 2022 in Europe and the OECD countries. Although previous evidence suggests that populist governance spells a rise in indebtedness, new evidence in this paper mitigates this conclusion. The results in this work do not provide sufficient evidence of an increase in debt specifically linked to populist governance. Three mechanisms may be at play. First, fiscal rules and checks and balances embedded in the democratic process in those countries make bad governance punishable in the following elections. Second, most populists in Europe and the OECD have so far been allocated junior coalition roles, limiting their potential damage on policy design and implementation. Third, the parliamentary democracies studied in this work may operate differently from the presidential regimes that have, until recently, dominated empirical evidence. As a result, most of the evidence in this work points to a relatively small, if at all significant, effect of populist governance on public debt. Nuances do emerge along the political spectrum, but they are evident after the Global Financial Crisis of 2008–2009.